2021
DOI: 10.1111/jog.14864
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian clear cell carcinoma with an immature teratoma component showing ARID1A deficiency and an identical PIK3CA mutation

Abstract: We herein report a case of ovarian clear cell carcinoma with an immature teratoma component that exhibited aggressive behavior. A 47-year-old woman presented with abdominal distention, and computed tomography detected a cystic mass on the right ovary. The resected mass had mural nodules, most of which showed a pale-yellow appearance; some nodules had a heterogeneous cut surface with bright yellow and white areas. Histologically, the former nodules were composed of clear cell carcinoma, while the latter contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Here, by using a panel comprised of 409 genes, we assessed the genomic characteristics of OCCC. As reported previously, we observed that ARID1A (49.1%) and PIK3CA (41.8%) were the most prevalent mutations [16,17,31,32]. Interestingly, given the population heterogeneity of the current and previous studies, the high presence of ARID1A and PIK3CA variants suggests that these are features specific to OCCC, rather than population ethnicity.…”
Section: Discussionsupporting
confidence: 76%
“…Here, by using a panel comprised of 409 genes, we assessed the genomic characteristics of OCCC. As reported previously, we observed that ARID1A (49.1%) and PIK3CA (41.8%) were the most prevalent mutations [16,17,31,32]. Interestingly, given the population heterogeneity of the current and previous studies, the high presence of ARID1A and PIK3CA variants suggests that these are features specific to OCCC, rather than population ethnicity.…”
Section: Discussionsupporting
confidence: 76%